Acclimation of anaerobic fermentation microbiome with acetate and ethanol for chain elongation and the biochemical response. (April 2023) - Li, Lin; Liu, Chang; Xu, Linji; Zhuang, Huichuan; He, Junguo; He, Qiang; Zhang, Jie
Abstract: Medium chain fatty acids (MCFAs) production is a promising method for resource recovery from organic wastes. In this study, the microbial community structure shift along the long-term acclimation experiment and the concomitant effect of H2 level on chain elongation performance was investigated. Chain elongation microbiome could be rapidly acclimated from traditional anaerobic fermentation consortia. Genera Caproiciproducens, Clostridium sensu stricto 12, Rummeliibacillus and Oscillibacter was found to be dominant during the operation. The H2 was accumulated in the headspace by increasing the ethanol input, which inhibited oxidation of caproate and butyrate immediately, while its inhibition effect on chain elongation was delayed. H2 level in the headspace was positively correlated to the MCFAs production related bacteria. However, too much H2 accumulated might be suppressive for MCFAs production in the long term. It might result from the thermodynamic barrier for discarding excess reducing equivalents under high H2 level, which further gave rise to ethanol accumulation in this system. Graphical abstract: Image 1 Highlights: Caproiciproducens, Clostridium sensu stricto 12 were the dominant key bacteria. High H2 level could inhibit MCFAs oxidation instantly. The H2 level displayed delayed effect on chain elongation performance. Thermodynamic characterization was depicted for chain elongation system. H2 level could cause electron transfer pathway alteration within the bacteria.